Environmental Policy under Imperfect Competition: A Survey - Till Requate (Kiel University, Department of Economics, 2005)
In this article I survey the theoretical literature on environmental policy in the presence of imperfect competition, ranging from early contributions in the 1960s to the present. I cover the following market structures when polluting firms have market power in the output market: monopoly, Cournot oligopoly, Bertrand duopoly with homogeneous products, pricesetting duopoly with differentiating commodities, and models of monopolistic competition. Among the latter I consider Cournot oligopoly with free entry, the Dixit-Stiglitz model, and Salop?s model of the circular city with polluting firms. The regulation instruments I concentrate on are emission taxes, tradable permits, and both absolute and relative standards. I also discuss taxation when firms have market power in the input market, and I study models where firms exercise market power in the market of tradable permits. In the latter case I also survey some recent results from the literature on experimental economics. Finally, I briefly discuss environmental policy in open economies when firms have market power in international markets. Here I suggest different decompositions of the unilateral second-best optimal tax rate, thus attempting to unify alternative interpretations of these decompositions in the literature.
Keywords: 330; Umweltpolitik; Umweltökonomik; Unvollkommener Wettbewerb; Theorie